2016
DOI: 10.1017/s1041610216000685
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving burden and gain among adult-child caregivers caring for parents with dementia in China: the partial mediating role of reciprocal filial piety

Abstract: The findings suggest that the effect of care recipient's BPSD on caregiver's burden/gain may be related to the level of RFP among adult-child caregivers in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 15 publications
0
35
0
2
Order By: Relevance
“…It dictates the expectations and obligations of children. Children are obligated to respect, care, greet, obey, and assure their parents' physical and emotional well-being (Yu et al, 2016;Dong, Zhang, & Simon, 2014). Discussing taboo topics such as ACP is viewed as upsetting, uncaring, and disrespectful to others.…”
Section: Intergeneration Differences and Acp In Chinese Americansmentioning
confidence: 99%
“…It dictates the expectations and obligations of children. Children are obligated to respect, care, greet, obey, and assure their parents' physical and emotional well-being (Yu et al, 2016;Dong, Zhang, & Simon, 2014). Discussing taboo topics such as ACP is viewed as upsetting, uncaring, and disrespectful to others.…”
Section: Intergeneration Differences and Acp In Chinese Americansmentioning
confidence: 99%
“…The number of people with dementia was over 9.5 million in 2015 and is expected to rise to over 16 million by 2030 (Jia et al, ; Wimo et al, ). Most people with dementia are cared for at home by unpaid family caregivers, of whom the majority (about 60%) are adult–child caregivers (Friedemann & Buckwalter, ; Yu et al, ). Existing research has revealed the high caregiving burden on adult–children of people with dementia (Svendsboe et al, ), which can lead to adverse health outcomes for these caregivers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, temporal and cognitive proportions for care at home are expected to be higher than those for care of other diseases or those with dementia without BPSD symptoms. Furthermore, Yu et al reported that having more symptoms of BPSD increased caregiving hours and burden of family caregivers . Hence, it is inferred that the family caregiver role and increased care burden create stress that is being carried over to work.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Yu et al reported that having more symptoms of BPSD increased caregiving hours and burden of family caregivers. 22 Hence, it is inferred that the family caregiver role and increased care burden create stress that is being carried over to work. In addition, employed family members who care for PWD in some cases might not respond flexibly to sudden BPSD due to the inability to adjust their work schedule.…”
Section: Discussionmentioning
confidence: 99%